HUBUNGAN MOTIVASI KERJA DENGAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT X DI KOTA BEKASI - Aisyah, Ratu Nur; Handayani, Handayani; Fikri, Ipik Muhammad (Jurnal Kesehatan, 2025)
Work motivation and job satisfaction are important factors that need to be considered by hospital management and health policy makers, especially for the nursing profession which often faces high demands and pressures. Aiming to analyze the relationship between work motivation and job satisfaction of nurses at Hospital X in Bekasi City. Involving a sample of 62 nurses with total sampling technique adjusted to the inclusion criteria. Using mixed method, quantitative includes univariate, bivariate, and multivariate while qualitative consists of data reduction analysis, data presentation and conclusions explained in narrative. The results showed that compensation motivation, working conditions, work facilities, work achievement, recognition from superiors and the job itself were significantly related pvalue <0.05 with job satisfaction of nurses of Hospital X in Bekasi City with dominant variables pvalue <0.05 namely compensation motivation, working conditions motivation, and working facilities motivation, while the most influential on job satisfaction was working conditions motivation with an OR level (9.072). The implications of this study indicate the need to provide salaries that are in accordance with standards, pay attention to aspects of the work environment, and improve work facilities in order to increase nurses' job satisfaction at Hospital X in Bekasi City